The History the Qur'anic Text from revelation to compilation; a Compative study with the Old and new testaments = Sejarah teks al Qur'an dari wahyu sampai kompilasi - M.M. Al Azami (Gema Insani, 2005)
ws.4/ws.c.1-4/nr,.05